COMMUNICATION IN THE CONTEXT OF DETERRITORIALIZATION: BETWEEN ALIENATION AND ADAPTATION - Abysova, Mariia (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Deterritorialization, as a process of losing traditional social, economic, and political ties, transforms communication mechanisms. The aim is to identify communicative mechanisms and strategies that either facilitate social adaptation or contribute to alienation in the context of deterritorialization. The tasks are: (1) to analyze deterritorialization in socio-philosophical concepts and define its communicative dimension; (2) to examine the role of communication in processes of social adaptation and alienation. Research methods include socio-philosophical analysis, a systems approach, the dialectical method, critical discourse analysis, and the hermeneutic approach. Research results. Deterritorialization alters social communication mechanisms, simultaneously creating conditions for both the integration and isolation of individuals. The removal of territorial constraints on communication promotes networked interaction while also deepening social alienation through algorithmic filtering of information and the reinforcement of informational segregation. Discussion. Deterritorialization is not an unambiguous process: it not only disrupts traditional social ties but also creates opportunities for new forms of integration. Further research may focus on analyzing hybrid forms of social inclusion that combine adaptive mechanisms with elements of alienation. Another promising avenue is the study of compensatory adaptation strategies, where individuals adjust to digital conditions without overcoming structural inequalities but merely adapting to their logic. Conclusions. Deterritorialization in the communicative dimension simultaneously expands social interaction and contributes to the fragmentation of society, altering mechanisms of control and regulation of information flows. It is accompanied by both new formats of inclusion and an intensification of alienation through the destabilization of social identity, informational segregation, and changes in communicative practices. Alienation manifests as a rupture between individuals and their social ties, leading to cognitive overload and informational isolation. Adaptation, in contrast, is possible through the reconfiguration of identity, overcoming segregation, and developing new communicative models. Flexible identity becomes a key mechanism for adjusting to changing conditions. Thus, communication in the context of deterritorialization serves a dual function: open and dialogical models foster integration, while algorithmic personalization reinforces social alienation, limiting the communicative possibilities of the subject.